STRUKTUR EKONOMI PROVINSI KALIMANTAN TIMUR - Fitriadi Fitriadi (FORUM EKONOMI, 2015)
Economic structure of the province of East Kalimantan, tend not to change because it is still dominated by mining and quarrying, manufacturing, and trade, hotels and restaurants as well as the agricultural sector, but the change in the contribution of each of these sectors.Â Keyword: Economic structure and contribution of economic sectors